THE PHENOMENON OF ARTIFICIAL INTELLIGENCE AS A FUTURE DREAM TECHNOLOGY ACCORDING TO HINDU'S TEACHINGS - I Wayan Dikse Pancane; Nyoman Dantes; Ni Nyoman Perni (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
Technological developments have made significant progress. One of them, namely the manufacture of computers designed to make it easier for humans to do their jobs. This advantage makes the role of humans reduced and displaced by the tools created by humans themselves. However, behind the sophistication of tools made by humans, stored the power of Ida Sang Yang Widi Wasa which is undetected and underappreciated. In fact, the manufacture of these tools turned out to be mirrored in the creation of Ida Sang Yang Widi Wasa, which was designed as if he wanted to emulate it. However, if explored and contemplated, Ida Sang Yang Widi Wasa's creation will not matched by the tools created by His own creation. Because nothing could match the creation of Ida Sang Yang Widi Wasa even though in the eyes of humans it is a monumental sophistication.